A review on machine learning techniques for text classification - Kavitha, M.; Prabhavathy, P. (2021 4th International Conference on Computing and Communications Technologies (ICCCT), 2021)
As the volume of information and documents available on the internet grows, so does the demand to access it, and the need for text classification becomes evident. Due to unstructured data, most businesses today are unable to realise their full potential. It is difficult to extract valuable insights from unstructured text data from various sources such as social media, emails, conversations, webpages, surveys, and it is also hard and time-consuming process. Companies can automate business processes and make data-driven business choices in a quick and cost-effective manner using machine learning text categorization algorithms. Scalability and real-time analysis are made easier by text tagging.